2018
DOI: 10.17501/icedu.2018.4109
|View full text |Cite
|
Sign up to set email alerts
|

Internet Usage and Juvenile Delinquency of High School Students in Surabaya Indonesia

Abstract: This research aimed to find out differences in juvenile delinquency based on the frequency of internet usage on high school students in Surabaya, Indonesia. Internet usage was measured based on the average frequency of daily use of the internet. Juvenile delinquency is students' tendency to violate regulations which can result in loss and damage both to oneself and others. This research used quantitative approach, involving 498 students from eight different schools in Surabaya, Indonesia. Data collection used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Pendidikan anak usia dini memiliki lima aspek perkembangan seperti nilai agama moral, fisik motorik, kognitif, Bahasa, sosial emosional. Pendidikan pada anak usia dini membutuhkan peran sekolah, keluarga dan masyarakat (Herdina Indrijati, 2016). Prinsip pembelajaran bagi anak usia dini adalah belajar melalui bermain.…”
Section: Pendahuluanunclassified
“…Pendidikan anak usia dini memiliki lima aspek perkembangan seperti nilai agama moral, fisik motorik, kognitif, Bahasa, sosial emosional. Pendidikan pada anak usia dini membutuhkan peran sekolah, keluarga dan masyarakat (Herdina Indrijati, 2016). Prinsip pembelajaran bagi anak usia dini adalah belajar melalui bermain.…”
Section: Pendahuluanunclassified
“…Indonesia as one of countries which supported the implementation of the international convention had ratified this principle into a formal regulation through child protection regulation number 35 (2014) to protect all Indonesia children from discrimination in various aspects so that they might obtain proper education, health coverage up to freedom to speak which may affect their future. There are many challenges occur related to child rights issues in Indonesia and some of them are related to parenting and basic issues, such as birth registration (Bennouna, Feldman, Usman, Adiputra, Kusumaningrum & Stark, 2016); juvenile delinquency (Indrijati, 2017;Erdianti & Al-Faith, 2019) up to child terrorism (Setiawan, Wardianti, Yusuf & Azikin, 2020). A study conducted by Duff, Kusumaningrum and Stark (2016) describes that one of causes that child is not registered through formal registration and obtain birth certificate is due to illegal marriage in some of districts in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…The National Police Headquarters in 2007 showed that 3,100 people involved in criminal cases were children under the age of 18 (BPS, 2010). Furthermore, the Indonesia National Child Protection Commission (KPAI) data showed that criminal acts involving children and adolescents were 35% higher from January to October, 2009, compared to previous years (Indrijati, 2017). Data in Jakarta, shows the pattern of juvenile delinquency has led to criminal acts (Detiknews, 2013).…”
Section: Introductionmentioning
confidence: 99%